1998
DOI: 10.1007/s004280050251
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cell differentiation in trichoblastoma

Abstract: Four cases of trichoblastoma rich in Merkel cells (MCs) are reported. They occurred in two men and two women, with ages ranging from 58 to 76 years (mean 67.5 years). MCs were detected immunohistochemically with antibodies to keratin 20, chromogranin A and neuron-specific enolase (NSE). In an attempt at better definition of the nature and role of MCs in trichoblastoma, the distribution of MCs in normal adult and fetal skins obtained at autopsy was studied. In addition, ten cases of sebaceous naevus of Jadassoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
3
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
0
27
3
2
Order By: Relevance
“…On rare occasions one can find abundant intratumoral MCs with only a few, if any, MCs in the overlying epidermis [14]. This phenomenon has only once been reported to occur in a small subset of TBs [14]but has never been confirmed in other investigations focused on MCs in this neoplasm [15, 16, 17, 18]. Our case demonstrated neither increased numbers of MCs in the tumor nor in the epidermis above the tumorous masses.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…On rare occasions one can find abundant intratumoral MCs with only a few, if any, MCs in the overlying epidermis [14]. This phenomenon has only once been reported to occur in a small subset of TBs [14]but has never been confirmed in other investigations focused on MCs in this neoplasm [15, 16, 17, 18]. Our case demonstrated neither increased numbers of MCs in the tumor nor in the epidermis above the tumorous masses.…”
Section: Discussionmentioning
confidence: 41%
“…Previous studies have shown that TB is typified by abundant MCs distributed in the tumor itself as well as in the overlying epidermis [13, 14, 15, 16, 17, 18]. On rare occasions one can find abundant intratumoral MCs with only a few, if any, MCs in the overlying epidermis [14].…”
Section: Discussionmentioning
confidence: 99%
“…Trichoblastoma often included focal positivity for synaptophysin, chromogranin A and cytokeratin 20, indicating neuroendocrine differentiation [4,13]. However, in the present case, many tumor cells were positive for synaptophysin, and focal positivity for Grimelius reaction and chromogranin A were seen.…”
contrasting
confidence: 41%
“…Merkel cells are regarded as a sign of follicular differentiation and have been found in both benign and malignant follicular neoplasms. [18][19][20][21][22][23][24][25][26] Squamous metaplasia has only rarely been specifically commented upon in the previously published material on tubular apocrine adenoma/papillary eccrine adenoma, although the descriptions of solid epithelial nodules, dilated cysts containing laminated keratin or squamous-cell-lined cysts almost certainly correspond to this phenomenon. [27][28][29][30] Murphy and Elder 30 suggested that dilated cysts containing laminated keratin may represent recapitulation of intraepidermal eccrine duct formation.…”
Section: Discussionmentioning
confidence: 98%